Pemetaan Permasalahan dalam Pelaksanaan Pagelaran Heman Ka Budak dalam Peningkatan Kebanggaan Budaya Sunda - Hanathasia, Mirana; Suharyanti; Kurnia, Ari (Indonesian Journal for Social Responsibility, 2019)
Preservation of local culture can be finish with various activities, which is an art performance. Through the Heman Ka Budak performance, conducted by Dinas Pendidikan dan Budaya (Disdikbud) of Kuningan District, West Java, it produces of arts and cultural-themed activities that are routinely every week at the Car Free Day event. The purpose of this Social Responsibility is to increase the pride of Sundanese culture by the community, especially teenagers and the support of many parties in preserving local culture. In dealing with the problem of lack of public awareness in preserving local culture, evaluations through the Focus Group Discussion (FGD) technique, which of Dinas Pendidikan dan Budaya (Disdikbud), artists as a participated in the activities of Heman ka Budak. In the FGD, Heman ka Budak activities faced of obstacles in the preservation this Sundanese culture. In addition to not getting funds to support activities, such as transportation costs for performers, consumption, and other technical costs, Mass Media to promotion and information also only uses Facebook and Instagram. There is no involvement of local and national Mass Media as well as sponsors of funding or products. So, local cultural preservation activities have not become a mass public concern, only held in the Kuningan District, West Java. The involvement of young people in this activity is only as a filler, not as long as they do promotions and publications as a pride towards the local culture.